Prints and Drawings acquired with the aid of the national art-collections fund. - National Gallery of Scotland, Edinburgh (Edinburgh : National Gallery of Scotland, 1983)
Testa, Pietro ; Castiglione, Giovanni Battista ; Sustris, Frederick ; Ingres, Jean-Auguste-Dominique ; Romney, George ; Cotes, Francis ; Dayes, Edward ; Gainsborough, Thomas ; etc.
Prints and Drawings acquired with the aid of the national art-collections fund, National Gallery of Scotland, Edinburgh, 1 May - 4 July 1983
boek